Characteristics of sleep architecture in autism spectrum disorders: A meta-analysis based on polysomnographic research. (February 2021) - Chen, Xin; Liu, Haixia; Wu, Yile; Xuan, Kun; Zhao, Tianming; Sun, Yehuan
Highlights: Autism spectrum disorders have attracted extensive attention in recent years, and their sleep problems are worthy further exploreding. Polysomnography is the gold standard for evaluating sleep disorders in autism spectrum disorders. Sleep problems are more prominent in autism spectrum disorders than in typically developed individuals while studies illustrating specific difference of sleep architecture between the twos systematically in the whole sleep cycle have not been found yet. Abstract: Eleven parameters recorded by polysomnography were used to evaluate the differences in sleep structure between individuals with autism spectrum disorders (ASDs) and typically developed individuals (TDs). Four databases (PubMed, Web of Science, Cochrane Library, and China National Knowledge Infrastructure (CNKI)) were searched for potentially relevant literature published before July 14, 2019. Data extraction was performed by two independent assessors. The Cohen's d effect sizes and their 95% confidence intervals (CIs) were calculated to assess the effectiveness with the random-effects model. The heterogeneity was estimated by Cochran's Q test. The research yielded 14 case-control studies, 11 of which were included in this meta-analysis. Synthesis of the differences in 11 sleep parameters between individuals with ASDs and TDs demonstrated the pooled effect size of Cohen'd was -0.52 (95% CI: (-0.97, -0.08)) for total sleep time (TST), -0.69 (95% CI: (-1.27, -0.11)) for sleep efficiency (SE%) and 0.93 (95% CI: (0.37, 1.48)) for stage 1 sleep (S1%), respectively. Our findings suggested that compared with TDs, individuals with ASDs tend to have a decreased TST and SE% and an increased S1%. Differences of characteristics of sleep architecture in other sleep parameters between individuals with ASDs and TDs were not found in this study.